2010
DOI: 10.1111/j.1551-2916.2010.03675.x
|View full text |Cite
|
Sign up to set email alerts
|

Large Electro‐Optic Effect in La‐Doped 0.75Pb(Mg1/3Nb2/3)O3–0.25PbTiO3 Transparent Ceramic by Two‐Stage Sintering

Abstract: Highly transparent ceramics of La‐doped 0.75Pb(Mg1/3Nb2/3)O3–0.25PbTiO3 were fabricated by a two‐stage sintering method from conventional raw materials. The ceramics exhibited a transparency as high as 65% for the infrared wavelength. Large quadratic electro‐optic coefficient of 66 × 10−16 (m/v)2 was obtained, which was the highest value reported so far in Pb(Mg1/3Nb2/3)O3–PbTiO3 ceramics. The ferroelectric phase inducing the threshold electric field Eth and the domain structure of the transparent ceramics wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 22 publications
1
50
0
Order By: Relevance
“…Furthermore, research about Eu‐doped transparent ceramics could be helpful in the search of new host materials with good chemical stability and high damage threshold for Eu 3+ since similar studies about Er‐doped 0.75PMN‐0.25PT ceramics has been conducted . Therefore, in this work, Eu‐doped 0.75PMN‐0.25PT transparent ceramics with different Eu concentrations were obtained by a two‐stage sintering method . The microstructure and variation of transmittance under electric field of Eu‐doped PMN‐PT transparent ceramics were studied and discussed.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, research about Eu‐doped transparent ceramics could be helpful in the search of new host materials with good chemical stability and high damage threshold for Eu 3+ since similar studies about Er‐doped 0.75PMN‐0.25PT ceramics has been conducted . Therefore, in this work, Eu‐doped 0.75PMN‐0.25PT transparent ceramics with different Eu concentrations were obtained by a two‐stage sintering method . The microstructure and variation of transmittance under electric field of Eu‐doped PMN‐PT transparent ceramics were studied and discussed.…”
Section: Introductionmentioning
confidence: 91%
“…Jiang et al reported a higher quadratic EO coefficient of R = 28 × 10 −16 (m/v) 2 in PMN‐PT systems . Ruan et al fabricated La‐doped 0.75PMN‐0.25PT transparent ceramics with a quadratic EO coefficient as high as R = 66 × 10 −16 (m/v) 2 and such giant electro–optic effect was believed to originate from the unstable ferroelectric state which would undergo field‐induced phase transition . Though La as a rare‐earth(RE) element has proved to be able to improve the transparency and EO performance of PMN‐PT transparent ceramics significantly, the detailed mechanism are still far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…5(A) shows the transmittance spectra of PLMNT transparent ceramics with the various PMN/PT ratios at different La contents. For the transparent materials, the theoretical transmittance T n should be described by the following equations [2]:…”
Section: Dielectric and Ferroelectric Propertiesmentioning
confidence: 99%
“…Electro-optic (EO) effect, i.e., the birefringence variation caused by an externally applied electric field, has potential applications in optical devices [1][2][3][4][5][6][7][8][9][10][11][12]. As EO benchmark materials, LiNbO 3 single crystals have been widely used in the field of current telecommunication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation